2008
DOI: 10.1002/pon.1453
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive effects of hormonal therapy in early stage breast cancer patients: a prospective study

Abstract: These data suggest that hormonal therapies exert a subtle negative influence on cognition in breast cancer patients. Further analyses indicated that this effect was not fully accounted for by demographic factors or fatigue. Methodological limitations of the current study are addressed, along with recommendations for future studies in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
125
4
14

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(154 citation statements)
references
References 53 publications
11
125
4
14
Order By: Relevance
“…Poorer performance on the AVLT learning delay test predicted difficulty meeting the mental and interpersonal demands of work. As other studies have shown, 33,34 reports of greater number of depressive symptoms were highly correlated with difficulties meeting the time management, physical, and mental/interpersonal demands of work as well as the overall percent of healthrelated work productivity loss.…”
Section: Discussionsupporting
confidence: 56%
“…Poorer performance on the AVLT learning delay test predicted difficulty meeting the mental and interpersonal demands of work. As other studies have shown, 33,34 reports of greater number of depressive symptoms were highly correlated with difficulties meeting the time management, physical, and mental/interpersonal demands of work as well as the overall percent of healthrelated work productivity loss.…”
Section: Discussionsupporting
confidence: 56%
“…Accordingly, adjuvant endocrine therapy in postmenopausal breast cancer may influence cognitive function. Tamoxifen was negatively associated with cognitive functions in some reports (Paganini-Hill & Clark 2000, Collins et al 2009) and the TEAM trial confirmed these findings by showing that tamoxifen is significantly associated with lower functioning in verbal memory and executive functioning (Schilder et al 2010). Exemestane, on the other hand, did not show significantly worse outcomes for any cognitive domain compared with healthy controls.…”
Section: Cognitionsupporting
confidence: 63%
“…Most of the participants in the present study showed no depression or anxiety. Moreover, the cognitive decline was not found among the patients who went into menopause or used some hormonal therapy, although menopausal status and hormone therapy might affect the cognitive function (38). These may have been related to the fact that the neuropsychological test results did not detect cognitive decline.…”
Section: Discussionmentioning
confidence: 93%